(untitled) (Estudios Sociales, 2025)
The purpose of this paper is to show the multiple ways in which the territory intervenes and is linked to institutions. For this purpose, the case of a secondary school in northern Patagonia, Argentina, is analyzed. It is a technical school with an agricultural orientation located 45 kilometers from the capital city of the province of Neuquén. From a qualitative work carried out in the year 2023, the findings are presented around the emerging dimensions, such as their origin, the obstacles, the networks that are generated there and the resistance actions that emanate from the subjects. It concludes with the importance of making visible the tensions, which, in turn, enable the school to occupy a place of utmost importance in the biography of its agents (teachers and students) and the community.